Improving Wear Resistance of DLC-Coated Metal Components During Service: A Review - Luji Wu; Zhongchao Bai; Qingle Hao; Jiayin Qin (Lubricants, 2025)
Diamond-like carbon (DLC) coatings have emerged as a focal point in advanced carbon materials research due to exceptional tribological properties, including ultralow friction coefficient, exceptional wear resistance, ultrahigh hardness, and chemical inertness. Deposition of DLC coatings on metal components represents an innovative solution to enhance wear resistance in engineering applications. However, suboptimal adhesion strength between coatings and substrates, coupled with inherent material limitations, critically compromises the tribological performance. This review systematically examines recent advances in improving the wear resistance of DLC-coated metal components. First, the fundamental wear mechanisms governing both metallic substrates and DLC coatings under service conditions are elucidated. Next, three pivotal technologies, substrate material treatment/strengthening, coating structure design, and elemental doping, all demonstrating significant efficacy in wear resistance enhancement, are critically analyzed. Furthermore, a comparative assessment of these techniques reveals the synergistic potential in hybrid approaches. Finally, a concise summary of the outlook is presented.